1997
DOI: 10.1159/000139467
|View full text |Cite
|
Sign up to set email alerts
|

Saturable Accumulation and Diuretic Activity of Hydrochlorothiazide in the Isolated Perfused Rat Kidney

Abstract: The role of tubular accumulation in renal disposition and diuretic efficacy of hydrochlorothiazide was studied in the isolated perfused rat kidney. Hydrochlorothiazide resulted in a dose-dependent increase in the fractional excretion of sodium, chloride and potassium, and in urinary flow and pH. Renal clearance of the drug was low as a result of a low extraction ratio and extensive nonionic back-diffusion. Hydrochlorothiazide was subject to saturable tubular secretion, following Michaelis-Menten kinetics. Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…However, as shown in Table 2, several organic anion uptake transporters may account for high intracellular concentrations in renal proximal tubule. We showed previously up to 20‐fold accumulation of salicyluric acid and hydrochlorothiazide in rat kidney ( Cox et al ., 1989 ; Masereeuw et al ., 1997 ), indicating that local proximal tubular concentrations may reach even higher levels. Furthermore, studies in Mrp4 knockout mice have shown that Mrp4 accounts for the luminal efflux of furosemide and hydrochlorothiazide at therapeutic plasma concentrations ( Hasegawa et al ., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown in Table 2, several organic anion uptake transporters may account for high intracellular concentrations in renal proximal tubule. We showed previously up to 20‐fold accumulation of salicyluric acid and hydrochlorothiazide in rat kidney ( Cox et al ., 1989 ; Masereeuw et al ., 1997 ), indicating that local proximal tubular concentrations may reach even higher levels. Furthermore, studies in Mrp4 knockout mice have shown that Mrp4 accounts for the luminal efflux of furosemide and hydrochlorothiazide at therapeutic plasma concentrations ( Hasegawa et al ., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Además, el potasio altera el gradiente de voltaje transepitelial, favoreciendo la reabsorción de sodio (14,15). Los datos de diuresis y excreción de electrolitos obtenidos en este estudio con la administración de S. scutellarioides son similares a los reportados con las tiacidas que actúan en el túbulo distal (16).…”
Section: Discussionunclassified
“…Probenecid, a uricosuric agent and a typical inhibitor of organic anion tubular secretion, markedly reduces the renal clearance of anionic diuretics such as furosemide and hydrochlorothiazide. 22,23 The transport of these compounds is further complicated by the observation that the uptake of PAH by OAT1expressing oocytes is reduced in the presence of thiazide diuretics, loop diuretics, and/or carbonic anhydrase inhibitors at clinically relevant concentrations. 24 Thus, these diuretics can out-compete PAH and other anions for transport sites.…”
Section: Drug Interactions With the Organic Anion Systemmentioning
confidence: 99%